Evaluation of current dryland training programm in alpine ski racers under 14 years in Alberta, Canada - Doyle-Baker, P.; Kashluba, K.; Clark, M.; Emery, C. (Science and Skiing VII, 2018)
This evaluation, combined with the existing evidence on NM training in team sports, provides important information for moving forward with a study in this under-researched group of U14 skiers (Emery et al., 2010). We did not measure the club's compliance rate to their dryland training program nor do we have a record of their program. Previously, it has been recognized that a lack of uptake and ongoing maintenance of NM programs is a concern (Richmond et al., 2011), and this will be particularly challenging in the club system of Alberta alpine ski racing. A future coach-delivered RCT will need to be very prescriptive and involve coach education as many coaches do not have any formalized training in strength and conditioning. Based on this evaluation, an NM training program delivered in a dryland program has the potential to improve performance outcomes associated with static and dynamic balance and be protective of lower-limb injuries in youth alpine racers.